Despatch from Professor D'Arcy Thompson forwarding a report on his mission to Behring Sea in 1897 : [In continuation of "United States no. 3 (1897)"] : Presented to both Houses of Parliament by command of Her Majesty : January 1898. - Thompson, D'Arcy Wentworth, 1860-1948. (London : Printed for Her Majesty's Stationery Office by Harrison and Sons, 1898)
Mode of access: Internet.